2020
DOI: 10.21037/qims-20-642
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of chest radiography for severe COVID-19

Abstract: Background: Chest radiography (CXR) is performed more widely and readily than CT for the management of coronavirus disease , but there remains little data on its clinical utility. This study aims to assess the diagnostic performance of CXR, with emphasis on its predictive value, for severe COVID-19 disease.Methods: A retrospective cohort study was conducted, 358 chest radiographs were performed on 109 COVID-19 patients (median age 44.4 years, 58 males and 30 with comorbidities) admitted between 22 January 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 26 publications
4
42
1
3
Order By: Relevance
“…In addition, there was a higher proportion of patients with severe COVID-19 experiencing fibrosis and air bronchogram [ 19 , 20 ]. An increasing trend in the prevalence of fibrosis occurrence in COVID-19 patients from admission to discharge was also observed and described in our study, which provides important information demonstrating the progress of fibrosis and lung damage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a higher proportion of patients with severe COVID-19 experiencing fibrosis and air bronchogram [ 19 , 20 ]. An increasing trend in the prevalence of fibrosis occurrence in COVID-19 patients from admission to discharge was also observed and described in our study, which provides important information demonstrating the progress of fibrosis and lung damage.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a retrospective cohort study of all COVID-19 patients with baseline CXR admitted to our center between January 22 and March 15 2020, as part of a separate study that developed a quantitative COVID-19 radiographic score [ 9 ]. During this study period, all patients with confirmed COVID-19 infection were admitted for inpatient care and isolation, regardless of disease severity.…”
Section: Methodsmentioning
confidence: 99%
“…Several quantitative CT radiographic scores have been developed to predict patients at risk of developing severe illness [ 7 , 8 ]. Recently, our group showed that an objective CXR radiographic score, modified from the Radiographic Assessment of Lung Edema (RALE) score for acute respiratory distress syndrome (ARDS), could quantify disease severity associated with supplemental oxygen requirement and mechanical ventilation, and could predict clinical deterioration if done within six to ten days from illness onset [ 9 ]. Borghesi et al have also demonstrated the value of CXR in assessing disease severity using a similar scoring system [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…When there was no disease progression after normal or mild findings were found on CXR, patients recovered after a relatively benign course of illness (cases 1 and 2). However, when disease progression in the form of bilateral consolidation with lower zone predominance that reached peak severity between days 10-12 was present, 18,19 patients deteriorated and required either supplemental oxygen therapy or mechanical ventilation (cases 3, 4 and 5).…”
Section: A B Cmentioning
confidence: 99%